Discovery of (phenylureido)piperidinyl benzamides as prospective inhibitors of bacterial autolysin E from Staphylococcus aureus - Jure Borišek; Sara Pintar; Mitja Ogrizek; Simona Golič Grdadolnik; Vesna Hodnik; Dušan Turk; Andrej Perdih; Marjana Novič (Taylor & Francis Group, 2018)
Autolysin E (AtlE) is a cell wall degrading enzyme that catalyzes the hydrolysis of the β-1,4-glycosidic bond between the N-acetylglucosamine and N-acetylmuramic acid units of the bacterial peptidoglycan. Using our recently determined crystal structure of AtlE from Staphylococcus aureus and a combination of pharmacophore modeling, similarity search, and molecular docking, a series of (Phenylureido)piperidinyl benzamides were identified as potential binders and surface plasmon resonance (SPR) and saturation-transfer difference (STD) NMR experiments revealed that discovered compounds bind to AtlE in a lower micromolar range. (phenylureido)piperidinyl benzamides are the first reported non-substrate-like compounds that interact with this enzyme and enable further study of the interaction of small molecules with bacterial AtlE as potential inhibitors of this target.